Strategic Management Accounting as a Driver of Climate Action Within Indonesian Enterprises - Yanuar Ramadhan; Yusup Setiawan; Ucok Jimmy (Yayasan Sinergi Kawula Muda, 2025)
Climate change is a global challenge that demands active responsibility from the corporate sector, particularly the energy industry, which is the largest contributor to carbon emissions in Indonesia. In this context, Strategic Management Accounting (SMA) plays a crucial role in integrating business strategy with sustainability objectives to support the achievement of Sustainable Development Goal (SDG) 13 – Climate Action. This study aims to analyze how SMA helps energy companies to design, implement, and evaluate climate strategies through governance mechanisms, management control systems, and environment-based performance metrics. This study offers a unique contribution by positioning SMA as an institutional mediator—a role that remains underexplored in the Indonesian context. The research employed a qualitative approach using the Systematic Literature Review (SLR) method. The study was conducted through the selection and synthesis of academic literature, research reports, and publications from international institutions relevant to the context of energy companies in Indonesia. The findings reveal that SMA acts as an institutional bridge connecting external pressures—such as regulatory mandates, investor expectations, and professional norms—with internal mechanisms like management control systems, performance metrics, and incentive structures. The integration of the Sustainability Balanced Scorecard (SBSC), carbon accounting, and internal carbon pricing enhances the alignment between financial performance and climate objectives. This study concludes that SMA plays a transformative role in embedding sustainability into corporate governance and operational systems. The findings underscore the need for corporate leaders and policymakers to strengthen SMA-based governance architectures, as doing so can significantly enhance Indonesia’s progress toward SDG 13 and accelerate its broader transition toward a low-carbon economy.